Microfibers in the Diet of a Highly Aerial Bird, the Common Swift Apus apus - Costanzo, Alessandra; Ambrosini, Roberto; Manica, Milo; Casola, Daniela; Polidori, Carlo; Gianotti, Valentina; Conterosito, Eleonora; Roncoli, Maddalena; Parolini, Marco; De Felice, Beatrice (Toxics, 2024)
Microplastic pollution is a pervasive global issue affecting various ecosystems. Despite the escalating production and well-documented contamination in both aquatic and terrestrial environments, the research focused on airborne microplastics and their interaction with terrestrial birds remains limited. In this study, we collected fecal sacs from Common swifts (Apus apus) to investigate their diet and to evaluate the potential ingestion of microplastics by both adults and nestlings. The diet was mainly composed of Hymenoptera and Coleoptera and did not differ among sexes and age classes. The 33% of nestlings' and 52% of adults' fecal sacs contained anthropogenic items, the totality of which was in the shape form of fibers. The 19.4% of the anthropogenic items were chemically characterized as microplastics, either polyethylene terephthalate (PET; two microfibers) or cellophane (four microfibers). Airborne anthropogenic items, including microplastic, might be passively ingested during the Common swift aerial feeding. In addition, our findings suggest that these ingested microparticles have the potential to be transferred to the offspring through food. While further research is essential to elucidate the pathways of microplastic ingestion, our results reinforce the evidence of the transfer of anthropogenic items from the atmosphere to the biota.